PELABELAN GRACEFUL GANJIL PADA GRAF DUPLIKASI DAN SPLIT BINTANG - Bantara, J A; Sudarsana, I W; Musdalifah, S (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2018)
Graph  is not an empty a finite of the objects that called point (vertex) with the couple was not that is the side (edge). The set point  denoted by , while the set edge denoted by . Odd graceful labeling on graph  with  side is a function injective from so that induced function  such that  in label with  so label sides would be different. A graph  that have an odd graceful labeling is called odd graceful graph. The result showed that duplicate star graph  for and split star graph  for , for  even satisfie odd graceful labeling.